Current evidence for the roles of early-life endocrine disruptors on pubertal timing in girls - Jeong Eun Lee; Hae Woon Jung; Yun Jeong Lee; Young Ah Lee (Korean Society of Pediatric Endocrinology, 2019)
Over the last decades, the onset of puberty in girls has occurred earlier, but the tempo of pubertal progression has been relatively slower, resulting in a younger age at puberty onset without a change in age at menarche. Sufficient energy availability and adiposity contribute to early pubertal development, and environmental factors, such as endocrine-disrupting chemicals (EDCs), may affect not only the control of energy balance, but also puberty and reproduction. EDCs are hormonally active substances that can perturb puberty by acting both peripherally on target organs, such as adipose tissue or adrenal glands, and/or centrally on the hypothalamic-pituitary-gonadal (HPG) axis. Depending on whether the exposure takes place earlier during fetal and neonatal life or later during early childhood, EDCs can lead to different outcomes through different mechanisms. Evidence of associations between exposures to EDCs and altered pubertal timing makes it reasonable to support their relationship. However, human epidemiologic data are limited or inconsistent and cannot provide sufficient evidence for a causal relationship between EDC exposure and changes in pubertal timing. Further investigation is warranted to determine the overall or different effects of EDCs exposure during prenatal or childhood windows on pubertal milestones and to reveal the underlying mechanisms, including epigenetic marks, whereby early-life exposure to EDCs affect the HPG-peripheral tissue axis.